Scientific output among thesis advisors: what is the situation of the nutrition undergraduate program in Peru? - Solís-Guevara, Fernando D. (2022)
Scientific output is an important indicator in the health field that should be assessed but has not been considered in the schools of nutrition. This paper aims to describe and characterize the scientific output among thesis advisors from a Peruvian private university’s school of nutrition. A descriptive-observational, cross-sectional and bibliometric research was conducted to determine the scientific output of 18 advisors of 57 undergraduate theses from a private university’s school of nutrition, which were accepted between 2013 and 2019. It was found that 66.70 % of the advisors had at least one scientific publication. Out of this group, 50.00 % and 38.90 % continued publishing in the following five and three years, respectively. Twenty-two point two zero percent (22.20 %) of the articles were published in Scopus database and 11.10 % in SciELO database. The scientific output accounted for 71 articles (written by 12 advisors), out of which 85.90 % were original papers, 91.50 % were open access publications, 78.90 % were written in Spanish and 22.50 % received funding. It is concluded that the scientific output among thesis advisors from a Peruvian private university’s school of nutrition was low in recent years.